(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
The developing environment created in preschool educational organizations should serve the qualitative, continuous, consistent and gradual implementation of the State Requirements for the Education and Training of Children and the requirements of the "First Step" State Program, taking into account the age aspects of children. The science and nature development center where the child works should be a source of information for the practical application of his knowledge and skills, a source that satisfies the child’s needs, encourages innovation, and improves his skills.